Factors affecting the effectiveness of biocementation of soil - Hanjiang Lai; Xingzhi Ding; Mingjuan Cui; Junjie Zheng; Jian Chu; Zhibo Chen (Biogeotechnics)
Microbially or enzyme induced carbonate precipitation has emerged to be a new type of soil improvement method. However, it appears that the biocementation process is affected by many factors and a common understanding on the control factors on the biocement effect has not been reached. This paper attempts to identify the main factors that controlling the MICP or EICP effect through an in-depth discussion on the fundamentals of biocementation process. Similar to other cemented granular materials, biocemented soil is a structural soil composite consisting of soil skeleton and biocement force chain or biocement network. The strength and stiffness of the biocemented soil is controlled by the reinforcement effect of the biocement network on the soil skeleton or the interplay of the soil skeleton and precipitates. The contribution of the strength by soil skeleton is affected by the soil types and soil properties, while the contribution of the precipitates is through the distribution of the biocement network and the properties of the precipitates.